Spatial Distribution of Reflectance Measurement for Solar Materials - Fabienne Sallaberry; Carlos Heras; Alberto García de Jalón; Raquel Erice; Cristina Pinto; Sonia Escorza Santos; Íñigo Salinas Áriz; David Martinez; Salvador Andrés; Alberto Bretón; Marcelino Sanchez (SolarPACES Conference Proceedings)
The spatial distribution of the reflected radiation by solar materials is a really important characteristic to be measured in order to obtain realistic optical simulation of solar systems. However, most of the instruments measure the hemispherical component of the reflected flux from materials. This study presents a new equipment composed of a semi-sphere with 62 detectors which measure the spatial distribution of reflectance from any material used in solar systems. The first tests and checking with this instrument have been presented in this paper.